Out-of-field doses for scanning proton radiotherapy of shallowly located paediatric tumours—a comparison of range shifter and 3D printed compensator. (25th January 2021) - Wochnik, A; Stolarczyk, L; Ambrožová, I; Davídková, M; De Saint-Hubert, M; Domański, S; Domingo, C; Knežević, Ž; Kopeć, R; Kuć, M; Majer, M; Mojżeszek, N; et al.
Abstract: The lowest possible energy of proton scanning beam in cyclotron proton therapy facilities is typically between 60 and 100 MeV. Treatment of superficial lesions requires a pre-absorber to deliver doses to shallower volumes. In most of the cases a range shifter (RS) is used, but as an alternative solution, a patient-specific 3D printed proton beam compensator (BC) can be applied. A BC enables further reduction of the air gap and consequently reduction of beam scattering. Such pre-absorbers are additional sources of secondary radiation. The aim of this work was the comparison of RS and BC with respect to out-of-field doses for a simulated treatment of superficial paediatric brain tumours. EURADOS WG9 performed comparative measurements of scattered radiation in the Proteus C-235 IBA facility (Cyclotron Centre Bronowice at the Institute of Nuclear Physics, CCB IFJ PAN, Kraków, Poland) using two anthropomorphic phantoms—5 and 10 yr old—for a superficial target in the brain. Both active detectors located inside the therapy room, and passive detectors placed inside the phantoms were used. Measurements were supplemented by Monte Carlo simulation of the radiation transport. For the applied 3D printed pre-absorbers, out-of-field doses from both secondary photons and neutrons were lower than for RS. Measurements with active environmental dosimeters at five positions inside the therapy room indicated that the RS/BC ratio of the out-of-field dose was also higher than one, with a maximum of 1.7. Photon dose inside phantoms leads to higher out-of-field doses for RS than BC to almost all organs with the highest RS/BC ratio 12.5 and 13.2 for breasts for 5 and 10 yr old phantoms, respectively. For organs closest to the isocentre such as the thyroid, neutron doses were lower for BC than RS due to neutrons moderation in the target volume, but for more distant organs like bladder—conversely—lower doses for RS than BC were observed. The use of 3D printed BC as the pre-absorber placed in the near vicinity of patient in the treatment of superficial tumours does not result in the increase of secondary radiation compared to the treatment with RS, placed far from the patient.